PARENTING MEMUPUK KECERDASAN ANAK SESUAI MINAT DAN BAKATNYA DI TK ABA IV MANGLI KABUPATEN JEMBER - Riyas Rahmawati (Kreasi: Jurnal Pengabdian Masyarakat, 2022)
Parenting is a very important thing for school institutions to provide knowledge to parents/guardians regarding education for early childhood. The aim of this parenting activity is to provide understanding and guidance to parents/guardians about how to cultivate children's intelligence according to their interests and talents. The activity method carried out is participatory, namely an effort to provide information to parents/guardians of students and teachers so that they have an increased understanding of the material presented. This form of community service activity takes the form of seminars and interactive discussions regarding the intelligence each child has and how to cultivate that intelligence according to the child's interests and talents. The result of this activity is the implementation of parenting activities for parents/guardians of students at Kindergarten ABA IV Mangli, Jember Regency in properly nurturing children's intelligence according to their interests and talents, as well as increasing the understanding of parents/guardians regarding how to cultivate children's intelligence according to their interests. and his talents.